Developing an Applied English Teaching Module for Culinary Vocational Students in the Merdeka Curriculum - Sudirman Sudirman; Mukhlidi Muskhir; Elida Elida; Yuliana Yuliana; Afdal Luthfi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Vocational education in Indonesia, particularly in the Culinary Expertise Program at SMK Negeri 1 Luak District, struggles to deliver English instruction that aligns with industry demands. Given English's role as a global language in the culinary sector, there is an urgent need for a contextualized, industry-relevant English curriculum. This study employed a Research and Development (RD) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Four expert validators, one English teacher, and 50 tenth-grade culinary students participated. Instruments included questionnaires, interviews, validation sheets, observation tools, and pre- and post-tests. Expert validation results indicated high content validity, with Aiken’s V values ranging from 0.83 to 0.95. The practicality test demonstrated that the module was highly usable in classroom settings. Moreover, students’ English proficiency in culinary contexts improved significantly, as reflected by N-Gain scores in the medium to high range. These findings suggest that the developed module effectively supports contextual English learning relevant to vocational culinary needs. Its high validity and practicality support its potential integration into the Merdeka Curriculum. The applied English module tailored to the culinary industry’s needs offers a practical and effective solution to enhance students' English skills, equipping SMK graduates with competencies essential for global workforce readiness.